Walking Outcome After Traumatic Paraplegic Spinal Cord Injury: The Function of Which Myotomes Makes a Difference?. (May 2023) - Cathomen, Adrian; Maier, Doris; Kriz, Jiri; Abel, Rainer; Röhrich, Frank; Baumberger, Michael; Scivoletto, Giorgio; Weidner, Norbert; Rupp, Rüdiger; Jutzeler, Catherine R.; Steeves, John D.; ,; et al.
Background: Accurate prediction of walking function after a traumatic spinal cord injury (SCI) is crucial for an appropriate tailoring and application of therapeutical interventions. Long-term outcome of ambulation is strongly related to residual muscle function acutely after injury and its recovery potential. The identification of the underlying determinants of ambulation, however, remains a challenging task in SCI, a neurological disorder presented with heterogeneous clinical manifestations and recovery trajectories. Objectives: Stratification of walking function and determination of its most relevant underlying muscle functions based on stratified homogeneous patient subgroups. Methods: Data from individuals with paraplegic SCI were used to develop a prediction-based stratification model, applying unbiased recursive partitioning conditional inference tree (URP–CTREE). The primary outcome was the 6-minute walk test at 6 months after injury. Standardized neurological assessments ≤15 days after injury were chosen as predictors. Resulting subgroups were incorporated into a subsequent node-specific analysis to attribute the role of individual lower extremity myotomes for the prognosis of walking function. Results: Using URP–CTREE, the study group of 361 SCI patients was divided into 8 homogeneous subgroups. The node specific analysis uncovered that proximal myotomes L2 and L3 were driving factors for the differentiation between walkers and non-walkers. Distal myotomes L4–S1 were revealed to be responsible for the prognostic distinction of indoor and outdoor walkers (with and without aids). Conclusion: Stratification of a heterogeneous population with paraplegic SCI into more homogeneous subgroups, combined with the identification of underlying muscle functions prospectively determining the walking outcome, enable potential benefit for application in clinical trials and practice.